Microfluidic Metasurfaces: A New Frontier in Electromagnetic Wave Engineering - Qin, Jin; Jiang, Shibin; Li, Shibin; He, Shaowei; Zhu, Weiming (Advanced Physics Research, 2024)
Metasurfaces, as 2D artificial electromagnetic materials, play a pivotal role in manipulating electromagnetic waves by controlling their amplitude, phase, and polarization. Achieving this control involves designing subwavelength meta‐molecules with specific geometries and periodicities. In the context of microfluidic metasurfaces, optical properties can be dynamically modulated by altering either the geometric structure of liquid meta‐molecules or the refractive index of the liquid medium. Leveraging the fluidity of liquid materials, microfluidic metasurfaces exhibit remarkable performance in terms of reconfigurability and flexibility. These properties not only establish a cutting‐edge research area but also broaden the scope of applications for active metasurface devices. Additionally, the integration of metasurfaces within microfluidic systems has led to novel functionalities, including enhanced particle manipulation and sensor technologies. Compared to conventional solid‐material‐based metasurfaces, microfluidic metasurfaces offer greater design freedom, making them advantageous for diverse fields such as electromagnetic absorption, optical sensing, holographic displays, and tunable optical meta‐devices like flat lenses and polarizers. This review provides insights into the characteristics, modulation techniques, and potential applications of microfluidic metasurfaces, illuminating both the current research landscape and promising avenues for further explorations. Leveraging the fluidity of liquid materials, microfluidic metasurfaces exhibit remarkable performance in terms of reconfigurability and flexibility. Additionally, the integration of metasurfaces within microfluidic systems leads to novel functionalities. Microfluidic metasurfaces offer greater design freedom, making them advantageous for diverse fields such as EM absorption, optical sensing, holographic displays, and tunable optical meta‐devices like flat lenses and polarizers.